, DMCN 43: 234–8 (Developmental Medicine and Child Neurology, 2001)
Aim To investigate the presence of accelerated long-term forgetting after a 7-day delay in children with neurofibromatosis type 1 (NF1), using an adapted verbal memory recall task, Experimental Word Recall Task (EWRT), and to examine its relationship with other cognitive abilities. Method This cross-sectional design involved 60 children with NF1 and 88 typically developing children who completed the EWRT and were aged between 6 years and 15 years 11 months. Statistical analyses were carried out in individuals who met the EWRT learning criteria (i.e., were able to successfully learn the list of words during the learning phase; NF1, n = 40, 19 females; typically developing, n = 84, 44 females). The EWRT was used to investigate accelerated long-term forgetting across delays of 2 and 30 minutes, and 7 days. Correlational analyses were used to examine the relationships between accelerated long-term forgetting and other cognitive measures in children with NF1. Results In the subset of children who were able to learn the EWRT criterion, there was no group difference in recall performance at a traditional delay interval of 30 minutes. Group differences were evident at a 7-day interval for recall and recognition. In children with NF1, this long-term forgetting (difference in proportion of recall between 7 days and 30 minutes) was not significantly associated with attention or working memory difficulties. Interpretation The study suggests that children with NF1 who can initially learn verbal information and retain it over a short delay of 30 minutes may forget this information at an accelerated rate compared to their unaffected peers. Findings may account for the reported subjective memory difficulties in children with NF1 despite normal performance on standardized memory tests. This insight challenges conventional perspectives on memory in children with NF1 and emphasizes the importance of extending assessment timelines beyond traditional boundaries.